Endoluminal functional lumen imaging probe: a new modality in the evaluation of esophageal disorders in children and preliminary use in eosinophilic esophagitis - Berson, Jenna; Kota, Archana; Levine, Jeremiah (Frontiers in Pediatrics, 2025)
IntroductionEvaluating pediatric esophageal motility and structural disorders such as eosinophilic esophagitis (EoE) remains challenging. Conventional modalities are limited in their ability to assess biomechanical properties of the gastrointestinal tract, such as luminal compliance and distensibility. The endoluminal functional lumen imaging probe (FLIP) is a minimally invasive technology that uses impedance planimetry to measure esophageal parameters. Recent studies have shown the utility of FLIP in quantifying esophageal remodeling and fibrostenotic severity. FLIP-derived esophageal distensibility index (DI) is a sensitive marker for subclinical fibrosis and rigidity, often identifying esophageal narrowing not apparent on endoscopy or by symptom assessment alone. We investigated the use of FLIP to capture early esophageal dysfunction in patients with EoE, especially those in clinical remission.MethodsRetrospective chart review of patients with EoE who underwent EndoFLIP at our institution. EndoFLIP 2.0 Impedance Planimetry System was used via standard protocol. Variables in patients with EoE were compared by unpaired t-test.ResultsTen patients fulfilled inclusion criteria and 70% of the cohort were in clinical remission. The average minimum diameter at the narrowest luminal point at the maximum fill volume was 11.3 mm ± 3.3. The average distensibility index was 3.1 mm2/mmHg ± 1.4.DiscussionEndoFLIP was able to detect esophageal dysfunction in pediatric patients with EoE as evidenced by an overall low distensibility index. This adjunctive tool appears particularly useful in asymptomatic patients with EoE in clinical and histologic remission, as it may detect residual esophageal dysfunction highlighting the importance of early detection and ongoing therapy.